Pengaruh Persepsi Kemudahan, Persepsi Manfaat dan Persepsi Resiko Terhadap Keputusan Penggunaan E-Wallet Pada Mahasiswa di Kota Jambi - Adinda Kirana; Agustina Mutia; Refky Fielnanda (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine the effect of perceived ease of use, perceived usefulness and perceived risks on the decision to use e-wallets among students in Jambi City. This research is a quantitative research, collecting data using questionnaires and questionnaires. The sample of this research is students who are in the city of Jambi, totaling 100 people. The results of this study show that the variables Perceived Ease of Use, Perceived Usefulness and Perceived Risk simultaneously influence the decision to use e-wallet. This result can be proven from the simultaneous f test value with a significance value of 0.000 <0.05 which means significant, the (partial) t-test results on the Perceived Ease of Use variable show that Perceived Ease of Use (X1) has a significant effect on the decision to use e-wallet, this is indicated by the t count > t table of 5,992 > 1.966 with a significance value of 0.000 < 0.05, the t-test results (partial) on the Perceived Usefulness variable show that Perceived Usefulness (X2) has a significant effect on the decision to use e- wallet, this is indicated by the t count > t table of 10,462 > 1.966 with a significance value of 0.000 <0.05 and the results of the t-test (partial) on the Perceived Risk variable show that Perceived Risk (X3) has a significant effect on the decision to use e-wallets, this is indicated by the value of t count > t table of 6,623 > 1.966 with a significance value of 0.000 < 0.05. And the R Square value is 0.642 or 64,2% which indicates that the independent variables have an influence of 64.2% on the use decision variable (Y).